Attachment, Social Support, Resilience and Posttraumatic Stress Disorder Symptoms in Chinese Adults Living with HIV/AIDS. Issue 2 (17th February 2018) - Wang, Qian; Zhou, Ting; Gao, Jun; Xu, Keyi; Qu, Wenyan; Yang, Yunping
ABSTRACT: The present study aimed to examine the effects of attachment, social support and resilience on posttraumatic stress disorder (PTSD) symptoms in people living with HIV/AIDS. One hundred fifty-two HIV+ adults in China were investigated. The results suggested that attachment anxiety had a significant direct effect on PTSD symptoms and impacted PTSD symptoms indirectly though associations with social support and resilience. Attachment avoidance could also be considered a distal risk factor of PTSD symptoms via the mediation of social support and resilience. The findings highlight the importance of identifying trauma and PTSD symptoms in people affected by HIV/AIDS and suggest that people with attachment anxiety and low social support resources might be at high risk for PTSD.